2010
DOI: 10.1021/ie100886n
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Reactive Distillation on the Yield of Tetraacetylethylenediamine (TAED)

Abstract: Determination of acetic anhydride and acetic acid concentrations in the distillate withdrawn from the distillation columnA mixture of acetic acid and acetic anhydride was charged in the reactor and subjected to distillation with total reflux. The mole fraction of acetic acid in the reflux was determined by using a refractometer (ATAGO, Model 3T) and a gas-chromatograph (Hewlett Packard,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Similarly, TAED could also activate SPB because it could undergo hydrolysis in the presence of water, producing hydrogen peroxide and borate, as shown in Equation 5, 27 which led to the generation of PAA molecules in the TAED/SPB system. Also, it was reported that the combination of TAED with SPC or SPB, especially in washing‐machine detergents, was able to effectively oxidise various chemical and biological compounds 20,28,46 . Meanwhile, peracetate was itself converted to acetate in these reactions 20 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, TAED could also activate SPB because it could undergo hydrolysis in the presence of water, producing hydrogen peroxide and borate, as shown in Equation 5, 27 which led to the generation of PAA molecules in the TAED/SPB system. Also, it was reported that the combination of TAED with SPC or SPB, especially in washing‐machine detergents, was able to effectively oxidise various chemical and biological compounds 20,28,46 . Meanwhile, peracetate was itself converted to acetate in these reactions 20 .…”
Section: Resultsmentioning
confidence: 99%
“…Also, it was reported that the combination of TAED with SPC or SPB, especially in washing-machine detergents, was able to effectively oxidise various chemical and biological compounds. 20,28,46 Meanwhile, peracetate was itself converted to acetate in these reactions. 20 On the other hand, SPS is known to be hydrolysed in water to produce hydrogen peroxide (Equation 6), which was then catalysed by TAED to promote dye decomposition.…”
Section: S C H E M Ementioning
confidence: 99%
“…Imides are highly important organic structures that are extensively found in various pharmaceuticals, natural products, and electrically conductive materials [19, 20] . Present methods for synthesis of imides most frequently utilize acylation of amides with acid chlorides in the presence of super‐stoichiometric amounts of strong bases [21, 22] .…”
Section: Figurementioning
confidence: 99%
“…Imides are highly important organic structures that are extensively found in various pharmaceuticals, natural products, and electrically conductive materials. [19,20] Present methods for synthesis of imides most frequently utilize acylation of amides with acid chlorides in the presence of super-stoichiometric amounts of strong bases. [21,22] Amides again are synthesized from the acylation of ammonia or primary amines with activated forms of carboxylic acids, such as acid chlorides, anhydrides, and esters.…”
mentioning
confidence: 99%
“…Reactive distillation (RD) is an option for the transesterification of methyl acetate with isobutanol, which is limited by chemical equilibrium. High conversions of reactants and high purities of products can be achieved by removing the products from the RD column. Therefore, many reversible reactions including esterification, transesterification, ,, hydrolysis, ,, etherification, and acetylation have been carried out in RD processes. In recent years, because of the excellent catalytic performance and easy recycling of ionic liquids, the RD process with ionic liquid as catalyst has attracted more attention.…”
Section: Introductionmentioning
confidence: 99%